The degree of implementing STEM practices among mathematics teachers at the middle school level from the teachers’ and educational supervisors’ perspectives - Almughyirah, Sultan Mubarak (International Journal of Innovative Research and Scientific Studies, 2024)
The current quantitative study aims to examine the degree of implementation of STEM practices among middle school mathematics teachers from the teachers’ and educational supervisors’ perspectives. The study also seeks to identify the statistical significance between the responses of teachers and supervisors regarding the degree of implementing STEM practices. STEM is an acronym for the integrative approach among science, technology, engineering and mathematics. The study used a questionnaire that was built based on a four-level Likert scale as a tool for collecting data using the descriptive survey method. Sixty-four middle school mathematics teachers and seven educational supervisors of mathematics participated in the study that took place in Al-Ahsa Governorate, Saudi Arabia. Findings revealed that the participating teachers implemented STEM practices moderately in their classrooms in the main three domains which are lesson evaluation, lesson implementation and lesson planning, respectively. In addition, there are statistically significant differences between the participating teachers and supervisors regarding the degree of implementing the STEM practices in favor of the teachers. The study recommends dedicating sufficient funds for STEM education, creating creative STEM websites and labs and obtaining access to STEM resources and materials. It is concluded that there is a great need for preparing mathematics teachers to apply STEM practices in their classrooms.